Accumulation of Metabolic Cardiovascular Risk Factors in Black and White Young Adults Over 20 Years. Issue 4 (24th April 2015) - Paynter, Nina P.; Kiefe, Catarina I.; Lewis, Cora E.; Loria, Catherine M.; Goff, David C.; Lloyd‐Jones, Donald M.
Abstract : Background: Cross‐sectional clustering of metabolic risk factors for cardiovascular disease in middle‐aged adults is well described, but less is known regarding the order in which risk factors develop through young adulthood and their relation to subclinical atherosclerosis. Method and Results: A total of 3178 black and white women and men in the Coronary Artery Risk Development in Young Adults study were assessed to identify the order in which cardiovascular disease risk factors including diabetes, hypertension, dyslipidemia (low high‐density lipoprotein cholesterol or high triglyceride levels), hypercholesterolemia (high total or low‐density lipoprotein cholesterol), and obesity develop. Observed patterns of risk factor development were compared with those expected if risk factors accumulated randomly, given their overall distribution in the population. Over the 20 years of follow‐up, 80% of participants developed at least 1 risk factor. The first factor to occur was dyslipidemia in 39% of participants, obesity in 20%, hypercholesterolemia in 11%, hypertension in 7%, and diabetes in 1%. Dyslipidemia was the only risk factor both to occur first and to be followed by additional risk factors more often than expected ( P <0.001 for both). Order of risk factor accrual did not affect subclinical atherosclerosis at year 20. Results were similar by sex, race, and smoking status. Conclusions: Multiple patterns of cardiovascular risk factor development were observed from young adulthood to middle age. Dyslipidemia, a potentially modifiable condition, often preceded the development of other risk factors and may be a useful target for intervention and monitoring.